Performance of the Vietnamese Automobile Industry - A Measurement using DEA - Tran, Duc Hiep (ĐHKT, 2016)
In Vietnam, the automobile industry was seen as a very important sector of the economy. This paper studies the efficiency and productivity change of the Vietnamese automobile industry during the 2004-2007 periods, employing the Malmquist - Data Envelopment Analysis approach. For the best of our knowledge, this is the first study to do so. Our findings showed that efficiency of the Vietnamese automobile firms were low, with the highest average score of 0.500 in 2007.